Idiopathic intracranial hypertension and bariatric surgery: a literature review and a presentation of two cases. (2nd January 2019) - Okoroafor, Francois; Karim, Muhammad Ali; Ali, Abdulmajid
Abstract: Objective: There is paucity of data concerning the impact of bariatric surgery on idiopathic intracranial hypertension (IIH). We therefore present the clinical course of two cases that were managed at our centre, which is a regional referral centre for bariatric surgery and present a literature review of patients with IIH who underwent bariatric surgery for the treatment of obesity. Method: Two patients were referred for bariatric surgery who were both morbidly obese and were diagnosed with IIH. One patient underwent bariatric surgery; the other patient's weight was managed conservatively. We followed up both patients for 2 years. PubMed was searched for published studies of patients with IIH undergoing bariatric surgery. Results: The patient that underwent weight loss surgery achieved sustained weight loss from 108kg to 87kg and gross resolution of their symptoms. The patient whose weight was managed conservatively lost weight initially and then put the weight back on. Her IIH symptoms persisted despite CSF shunt therapy. The literature review identified 12 original studies, containing 51 patients. Weight loss after bariatric surgery was reported for 84% of patients and improvement or resolution of IIH symptoms was reported for 84% of patients. Conclusion: In light of the literature review and our experience, bariatric surgery appears to be a potential treatment option for IIH alongside the comorbidities associated with obesity. However, more robust studies are needed.